Market and Socio-cultural Embeddedness (A Case of ‘Subhan’s Beauty Home’, Bhaktapur and ‘Ason’ Market, Kathmandu) - Raut, Sunita (Bagiswori Journal, 2022)
Famous political economist Adam Smith argued that the market economy is made up of a series of individual exchanges or transactions which automatically create a functioning and ordered system. Similarly, according to rational choice theory, capitalist economy is driven by individual self-interest and works best when individual buyers and sellers make rational decisions that serve their own interests. In contrast to this atomized economic approach of David Ricardo, Adam Smith and others, this research paper entitled ‘market and social embeddedness’ applies Granovetter’s ideas of ‘social embeddedness of market’ and highlights an alternative way of analyzing economic institutions and market which operate and functioned with non-economic institution, which is broadly functions within larger social and cultural framework with reflective empirical evidences. This article discusses the issues based on the data gathered from the two case studies through interview tool. The nature of study is qualitative and cases were selected purposively. The major purpose of this article is to prove that, market co-exist with, shaped by and depend on socio-cultural factor and moral values not only under socialized economic behaviors one. The theory which I applied in this study is reflected and supported with cases as market is constructed and functions with the relation of social and non-social economic factors. The major findings of this study are persons with long-term socio-cultural ties, established social networks, confidence, and quality sensitivity engage in economic transactions in the market rather than strangers one. People make their decisions on goods and services on their previous dealings and moral values with service provider or businessman then continue to deal with those they trust not only by the individualistic market-oriented transaction.